Patterns of Facial Fractures and Associated Soft Tissue Injuries: A Retrospective Study on 1007 Patients - Raluca-Iulia Juncar; Paul Andrei Tent; Antonia Harangus; Mihai Juncar (Acta Clinica Croatica, 2022)
Background: Knowing the severity of a pathology in a population helps to both establish a rapid diagnosis and to prepare medical staff to provide adequate and complete treatment. The aim of this study was to determine the patterns of maxillofacial fractures and their associated soft tissue injuries in order to identify the specific types of maxillofacial fractures with the highest incidence of associated soft tissue injuries. Methods: A 10-year retrospective evaluation of maxillofacial trauma was performed on 1007 patients. All 1007 patients were clinically and paraclinically confirmed to have facial skeletal injuries. Results: The highest incidence of maxillofacial fractures was found in the mandible (62.16%), the mandibular angle being the most frequently involved (28.84%). Most of the fractures were complete (97.82%), displaced (87.98%) and closed (86.30%). Hematoma was the most common associated soft tissue injury (44.79%). In mandibular trauma, the incidence of hematoma and laceration was the highest in angle and simultaneous multiple fracture lines (p=0.002). In the midface, hematoma was more frequently associated with non-comminuted zygomatic bone fractures (p=0.003), while laceration was associated with multiple underlying fracture lines (p=0.002). Conclusions: Patients presenting with hematomas will most frequently have an underlying single closed fracture line, while patients with lacerations will most frequently present underlying multiple and displaced fractures.